Paternal Structures of the Romance - Malinowska, Anna (Romanica Silesiana)
The paper is a critical analysis of romance fiction in relation to parental structures visible in patriarchal codes and paternal tropes romance novels pivot around. As such, it provides an insight into the narrative patterns the romance uses to sustain patriarchy as well as recreate the father‑daughter‑like relationship at the center of cultural practices of love.